2005
DOI: 10.4049/jimmunol.174.5.3015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Apoptotic Cell Clearance Capacity and B Cell Survival Factor Production by IL-10-Activated Macrophages: Implications for Burkitt’s Lymphoma

Abstract: Burkitt’s lymphoma (BL) is typified by frequent tumor cell apoptosis and significant macrophage infiltration. Since BL cells have an inherent tendency to undergo apoptosis at a high rate, we reasoned that macrophages in BL are functionally enhanced in at least two activities that have implications for tumor pathogenesis: 1) engulfment of apoptotic cells, an anti-inflammatory process known to suppress immune responses, and 2) production of BL cell survival factors that limit the extent of tumor cell apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 59 publications
4
96
1
3
Order By: Relevance
“…It has been shown that macrophages, regulated by IL-10, have the potential to promote BL pathogenesis, firstly, through suppression of antitumor immunity following enhanced engulfment of apoptotic tumor cells and, secondly, through increased production of tumor cell growth/ survival factors. 75 In summary, this study reveals a novel physiological role of PARP-1 in the regulation of IL-10 induced uniquely by apoptotic cell-derived signals, and provides a clear molecular mechanism whereby individual IL-10 promoter haplotypes confer differential IL-10 production. Further investigation and elucidation of the molecular nature and characteristics of PARP-1-mediated immunoregulation will likely benefit the design of effective therapeutic strategies against a wide range of inflammatory and pathological conditions such as SLE, arthritis, asthma, sepsis, cardiomyopathy, stroke, inflammatory bowel disease, diabetes and cancer.…”
Section: Parp-1 Regulates Il-10 Snp-mediated Transcriptionmentioning
confidence: 76%
“…It has been shown that macrophages, regulated by IL-10, have the potential to promote BL pathogenesis, firstly, through suppression of antitumor immunity following enhanced engulfment of apoptotic tumor cells and, secondly, through increased production of tumor cell growth/ survival factors. 75 In summary, this study reveals a novel physiological role of PARP-1 in the regulation of IL-10 induced uniquely by apoptotic cell-derived signals, and provides a clear molecular mechanism whereby individual IL-10 promoter haplotypes confer differential IL-10 production. Further investigation and elucidation of the molecular nature and characteristics of PARP-1-mediated immunoregulation will likely benefit the design of effective therapeutic strategies against a wide range of inflammatory and pathological conditions such as SLE, arthritis, asthma, sepsis, cardiomyopathy, stroke, inflammatory bowel disease, diabetes and cancer.…”
Section: Parp-1 Regulates Il-10 Snp-mediated Transcriptionmentioning
confidence: 76%
“…An interaction between TAM and cytokine receptors during homeostatic phagocytosis has not been clearly demonstrated. However, IL-10 has been found to stimulate the phagocytosis of apoptotic cells by monocytes and macrophages 53,54 , and GAS6 and MER are among the monocyte genes that are upregulated by IL-10 (REF. 55 ).…”
mentioning
confidence: 99%
“…17 Like IL-6, high levels of IL-10 in eBL tumor microenvironment also seem to be important in tumorigenesis and growth through multiple mechanisms. 15 It has been shown to be an autocrine growth factor for Burkitt-derived cell lines, 18,19 and it is frequently expressed in various B-cell malignancies. 14,20 IL-10 has been well-characterized as a protumorigenic cytokine with immunosuppressive effects by way of inhibition of interferon-γ, proinflammatory T-helper-1 lymphocytes, and cytotoxic T cells, 21 which are central mediators in control of EBV; hence, they potentially contribute to EBV and tumor escape from immune surveillance and enhance tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…14 Both IL-6 and IL-10 have been shown to be highly expressed in the BL tumor microenvironment, suggesting that they may be important signals in tumorigenesis. 15,16 IL-6 acts as a growth factor for EBV-infected B cells, resulting in increased Ig production and B-cell immortalization. 16 It has also been shown to be highly expressed in EBVimmortalized B cells, thereby promoting tumor growth.…”
Section: Introductionmentioning
confidence: 99%